IMPROVEMENT OF THE COLONIZED WINDOW OF UXK TYPE COTTON CLEANING EQUIPMENT FROM SMALL AND LARGE POLLUTION (Journal of Science-Innovative Research in Uzbekistan, 2024)
The colosnik grid of uxk cleaning line was improved and the cleaning efficiency was increased, which economically benefited the cotton ginning plant